Design of Integrated Data Management System for Sustainability Reporting and Program for Manufacturing Industries in Indonesia - Priskila Christine Rahayu; Daisy Amanda; Jessica Hanafi (Indonesian Journal of Life Cycle Assessment and Sustainability, 2018)
The    manufacturing    industry    and    its relationship with sustainable development simply cannot be separated.  Especially,  when  the  government  started  to  show their   attention   by   giving   various   obligations   for   the manufacturing industry to implement sustainable development   principles,   such   as   the   obligation   of   the company     to     conduct     a     social     and     environmental responsibility  by  making  sustainability  report,  the environmental impact assessment (AMDAL) report,  to  participate  in  various  sustainability  programs such  as  Corporate Performance Rating Program (PROPER)  and  Green  Industry  Award.  There  are  so many  indicators  and  data  that  need  to  be  collected  in  order to   fulfill   these   obligations.   It   certainly   may   charge   the company in terms of time, yet the number of indicators and the   data required were similar between one report to another.  There is still no particular design to be able to resolve the issue. Therefore, the aim of this study is to design an  integrated  data  management  system  for  sustainability reporting  needs  and  sustainability  programs  which  has  the end  result  of  an application  prototype  of  a  system  that  can help  companies,  especially  in  the  manufacturing  industry  to create  reporting  even  more efficient.  Data  management  is done  by  combining  all  four  types  of  reporting  and  program which  are  Global Report Initiative sustainability  report,  the  AMDAL  report, Green  Industry  program,  and  PROPER.  The  prototype  is made   based   on   the   results   of   data   management   using Microsoft  Access  to  store  data  and  to  produce  four  types  of summary   reports.   In   the   end   of   the   study,   it   can   be concluded  that,  overall,  the  system  can  be  implemented  and by  the  withdrawal  of  three  respondents review,  the  system can  improve  the efficiency of  the  company  in  preparing sustainability reporting. In the evaluation phase, it is found a related  method  that  can  be  used  as  the basis  to  do  before making reporting in order to make them more easily 40.98%, that is Life Cycle Assessment.